Defining poverty as distinctively human - Lötter, H. P. P. (HTS teologiese studies, 2007)
While it is relatively easy for most people to identify human beings suffering from poverty, it is rather more difficult to come to a proper understanding of poverty. In this article the author wants to deepen our understanding of poverty by interpreting the conventional definitions of poverty in a new light. The article starts with a defence of a claim that poverty is a concept uniquely applicable to humans. It then present a critical discussion of the distinction between absolute and relative poverty and it is then argued that a revision of this distinction can provide general standards applicable to humans everywhere.